2014
DOI: 10.1016/j.febslet.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

miR‐342‐3p suppresses proliferation, migration and invasion by targeting FOXM1 in human cervical cancer

Abstract: Edited by Tamas DalmayKeywords: miR-342-3p EVL Forkhead Box M1 Cervical cancer a b s t r a c t FOXM1 is a well-established oncogenic factor that has been reported to be involved in multiple biological processes including cell proliferation, growth, angiogenesis, migration and invasion. It can also be regulated by miRNAs. In this study, we reported that FOXM1 is directly targeted by miR-342-3p, which is down-regulated along with its host gene, EVL, in human cervical cancer tissues compared to the adjacent norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
81
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 25 publications
7
81
0
1
Order By: Relevance
“…For instance, Zhou et al (26) demonstrated that that miR-107 directly targeted myeloid cell leukemia-1 and activated the ATR serine/threonine kinase/checkpoint kinase 1 pathway to inhibit the proliferation, migration and invasiveness of cervical cancer cells. Li et al (27) reported that the overexpression of miR-342-3p inhibits cell proliferation, migration and invasion in cervical cell lines by targeting mammalian transcription factor forkhead box M1. Wen et al (28) reported that miR-506 induced cell cycle arrest at the G1/S transition, enhanced the apoptosis and chemosensitivity of cervical cancer cells, and inhibited cervical cancer growth in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhou et al (26) demonstrated that that miR-107 directly targeted myeloid cell leukemia-1 and activated the ATR serine/threonine kinase/checkpoint kinase 1 pathway to inhibit the proliferation, migration and invasiveness of cervical cancer cells. Li et al (27) reported that the overexpression of miR-342-3p inhibits cell proliferation, migration and invasion in cervical cell lines by targeting mammalian transcription factor forkhead box M1. Wen et al (28) reported that miR-506 induced cell cycle arrest at the G1/S transition, enhanced the apoptosis and chemosensitivity of cervical cancer cells, and inhibited cervical cancer growth in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of miR-342-3p has been associated with significantly worse survival in patients with colon cancer [50]. More recently, it has been reported that miR-342-3p suppresses proliferation, migration and invasion by targeting FOXM1 in human cervical cancer [51]. This miR has also been found to be significantly elevated in irritable bowel syndrome patients [52].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that, during the embryonic period, FOXM1 is overexpressed in all tissues (15); however, in adulthood, FOXM1 expression only occurs in the tissues with active proliferation and metabolism (16). In various types of tumor cells, FOXM1 is highly expressed in the nucleus and cytoplasm, and causes the dysfunction of regulation processes (17)(18)(19)(20)(21). In particular, FOXM1 controls mitotic entry by the periodic upregulation of a group of genes that are maximally expressed as cells progress through the late G2 and into the M phase (14).…”
Section: Introductionmentioning
confidence: 99%